Sarcosine Suppresses Epileptogenesis in Rats With Effects on Hippocampal DNA Methylation - Shen, Hai-Ying; Weltha, Landen; Cook, John M.; Gesese, Raey; Omi, Wakaba; Baer, Sadie B.; Rose, Rizelle Mae; Reemmer, Jesica; Boison, Detlev (Frontiers in Molecular Neuroscience, 2020)
Epileptogenesis is a common consequence of brain insults; however, the prevention or delay of the epileptogenic process remains an important unmet medical challenge. Overexpression of glycine transporter 1 (GlyT1) is proposed as a pathological hallmark in the hippocampus of patients with temporal lobe epilepsy, and we previously demonstrated in rodent epilepsy models that augmentation of glycine suppressed chronic seizures and altered acute seizure thresholds. In the present study we evaluated the effect of the GlyT1 inhibitor, sarcosine (aka N-methylglycine), on epileptogenesis and also investigated possible mechanisms. We developed a modified rapid kindling model of epileptogenesis in rats combined with seizure score monitoring to evaluate the antiepileptogenic effect of sarcosine. We used immunohistochemistry and Western blot analysis for the evaluation of GlyT1 expression and epigenetic changes of 5-methylcytosine (5mC) and 5-hydroxymethylcytosine (5hmC) in the epileptogenic hippocampi of rats, and further evaluated expression changes in enzymes involved in the regulation of DNA methylation, ten-eleven translocation methylcytosine dioxygenase 1 (TET1), DNA-methyltransferase 1 (DNMT1), and DNMT3a. Our results demonstrated: (i) experimental evidence that sarcosine (3g/kg, i.p. daily) suppressed kindling epileptogenesis in rats; (ii) the sarcosine-induced antiepileptogenic effect was accompanied by a suppressed hippocampal GlyT1 expression as well as a reduction of hippocampal 5mC levels and a corresponding increase in 5hmC; and (iii) sarcosine treatment caused differential expression changes of TET1 and DNMTs. Together, these findings suggest that sarcosine has unprecedented disease-modifying properties in a kindling model of epileptogenesis in rats, which was associated with altered hippocampal DNA methylation. Thus, manipulation of the glycine system is a potential therapeutic approach to attenuate the development of epilepsy.